Pengaruh Formulasi Tepung Ubi Jalar Ungu dan Mocaf Terhadap Karakteristik Fisikokimia Gluten-Free Cookies - Zulkarnaen Zulkarnaen; Ni Wayan Putu Meikapasa; Husnita Komalasari (Universitas Bumigora, 2026)
Gluten-free cookies are a type of biscuit developed as a dietary alternative for individuals with gluten intolerance, while also supporting food diversification through the use of local raw materials rich in carbohydrates and functional components. This study aims to analyze the effect of formulations containing purple sweet potato flour and mocaf on the physicochemical properties of gluten-free cookies. This study employed an experimental method using a one-factor completely randomized design with three treatmentswith different proportion of mocaf:purple sweet potato flour, P1 (30%: 70%), P2 (50%: 50%), and P3 (70%: 30%). The parameters analyzed included moisture content, crude fiber content, hardness, color (L*, a*, and b*), and spread ratio. The data were statistically analyzed using ANOVA and followed by a post-hoc test for significant differences at a 5% significance level (P < 0.05). The results showed that variations in formulation had a significant effect on moisture content (3.42%–5.77%), crude fiber content (2.34%–3.55%), hardness (4.58–38.47 g), L* value (36.32–52.69), b* value (3.00–5.53), and spread ratio (3.00–5.53). Thus, the conclusion of this study is that differences in the formulations of purple sweet potato flour and mocaf were shown to affect the physicochemical characteristics of gluten-free cookies. It is hoped that this study can serve as a basis for the development of gluten-free cookies based on Local Food Resources.